2020
DOI: 10.1159/000513040
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of SARS-CoV2 Entry Protein ACE2 in the Human Nose and Olfactory Bulb

Abstract: Usually, pandemic COVID-19 disease, caused by SARS-CoV2, presents with mild respiratory symptoms such as fever, cough, but frequently also with anosmia and neurological symptoms. Virus-cell fusion is mediated by angiotensin-converting enzyme 2 (ACE2) and transmembrane serine protease 2 (TMPRSS2) with their organ expression pattern determining viral tropism. Clinical presentation suggests rapid viral dissemination to the central nervous system leading frequently to severe symptoms including viral meningitis. He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 31 publications
2
53
0
1
Order By: Relevance
“…In humans, the number of nervus terminalis neurons is relatively small (a few hundred to a few thousand neurons depending on age, Brookover, 1917;Larsell, 1950;Jin et al, 2019). However, such a relatively small number may be sufficient to mediate viral infection, especially considering that the nervus terminalis directly innervates secretory cells of the Bowman's glands (Larsell, 1950) that are known to express ACE2 (Brann et al, 2020;Chen et al, 2020;Cooper et al, 2020;Ye et al, 2020;Zhang et al, 2020;Klingenstein et al, 2021) and readily become infected with SARS-CoV-2 (Ye et al, 2020;Leist et al, 2020;Meinhardt et al, 2020;Zhang et al, 2020;Zheng et al, 2020) (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the number of nervus terminalis neurons is relatively small (a few hundred to a few thousand neurons depending on age, Brookover, 1917;Larsell, 1950;Jin et al, 2019). However, such a relatively small number may be sufficient to mediate viral infection, especially considering that the nervus terminalis directly innervates secretory cells of the Bowman's glands (Larsell, 1950) that are known to express ACE2 (Brann et al, 2020;Chen et al, 2020;Cooper et al, 2020;Ye et al, 2020;Zhang et al, 2020;Klingenstein et al, 2021) and readily become infected with SARS-CoV-2 (Ye et al, 2020;Leist et al, 2020;Meinhardt et al, 2020;Zhang et al, 2020;Zheng et al, 2020) (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Cells expressing ACE2 are indicated in green, including sustentacular cells (SUS) and BG cells. Both of these cell types have been shown to express ACE2 (Bilinska et al, 2020;Brann et al, 2020;Chen et al, 2020;Ye et al, 2020;Zhang et al, 2020;Klingenstein et al, 2021). Cell types that have been documented to be infected by SARS-CoV-2 are indicated with pink asterisks.…”
Section: Contribution To the Fieldmentioning
confidence: 99%
“…To assess whether olfactory receptor neurons may be susceptible to infection by SARS-CoV-2, investigators have determined which cell types in the olfactory epithelium express the obligatory entry proteins for the new coronavirus, angiotensin-converting enzyme 2 (ACE2) and transmembrane protease, serine 2 (TMPRSS2). These gene and protein expression studies were performed by RNAseq of identified cell types, or using markers for distinct cell types within the olfactory epithelium combined with gene or protein expression for ACE2 and TMPRSS2 [6,8,11,23,38,42,52,66,98,103,106]. The large majority of these studies concluded that sustentacular cells (the primary support cells in the olfactory epithelium) and cells in Bowman's glands express the virus entry proteins, while all human studies and the majority of animal studies reported that olfactory receptor neurons do not express ACE2, or express ACE2 only very rarely (Tables 1, 2 and 3).…”
Section: Can Olfactory Neurons Become Infected By Sars-cov-2?mentioning
confidence: 99%
“…About 11% of those patients developed anosmia prior to any other clinical symptoms (Lechien et al, 2020). ACE2 has been found to be highly expressed in nasal goblet and ciliated cells, which strongly indicates the possibility that SARS-CoV-2 may enter the human brain through olfactory nerves (Klingenstein et al, 2021). Another potential invading route for SARS-CoV-2 is probably via ventricular choroid plexus into cerebrospinal fluid (CSF) and brain (Abate et al, 2020).…”
Section: Covid-19 and Alzheimer's Diseasementioning
confidence: 99%